100k views
4 votes
Can anyone do this quick please ​

Can anyone do this quick please ​-example-1
User Ashish M
by
5.8k points

2 Answers

4 votes
-3 because -8 plus -2 equal 10 and 6 plus - 1 equal 7 they need -3 to get to 10
User Tim Perkins
by
5.6k points
3 votes

I just did this one because it said distance formula of points. I don't know what the second line is saying.

Explanation:

A (-8,-2) = (x1, y1)

B (6,-1) = (x2,y2)

now,

distance formula,

=


\sqrt( x2+ x1)^(2) + (y2 - y1) ^(2)

=


\sqrt( 6 + 8)^(2) + ( - 1 + 2)^(2)

=


\sqrt(14)^(2) - (1)^(2)

=


\sqrt(196 - 1)

=


√(195)

User Max Schilling
by
4.8k points